Experimental study of axial compression behavior of circular concrete-filled steel tubes after being loaded at an early age. (20th September 2021) - Zhang, Ji; Ma, Lu; Zhou, Changlin; Lee, Dongkyu; Filippou, Filip C.
Highlights: Tests on effects of CFST very early age loading on long-term behaviors conducted. Long-term ultimate capacity and yield loads improved by very early age loading. Long-term combined elastic moduli increased by very early age loading. Abstract: This paper presents an experimental study on the effects of very early age loading of concrete-filled steel tubular (CFST) short columns on their long-term axial compression behaviors. The specimens include CFSTs wrapped in FRP (fiber reinforced polymer) cloths and bare CFSTs. When concrete is at an age of 1d, 2d or 3d, the circular CFST column specimen is loaded with axial compression, unloaded after reaching the peak value, and then put into the curing room to continue curing. At the age of 28d, the axial compression bearing capacity is tested and the load–displacement curve is obtained. In the tests, five CFST columns are set as the control group, which are directly cured until 28d. The effects of initial loading age, steel tube wall thickness and constraint level are investigated. The results show that very early age loading can improve the long-term load bearing performance of CFST columns. For the configurations applied in the present study, the ultimate bearing capacity are increased by 1.01% to 24.59%, the yield loads by 2.33% to 52.53%, and the combined elastic moduli are also increased.